Proceedings of the 50th Annual Conference on Computers and People Research 2012
DOI: 10.1145/2214091.2214141
|View full text |Cite
|
Sign up to set email alerts
|

Embracing intersectionality in gender and IT career choice research

Abstract: Results of an examination of with-gender variation in gender stereotypes about the skills and knowledge in the IT profession demonstrates the value of applying an intersectionality perspective in the study of under represented groups in the IT field. Focusing on gender or ethnicity, alone, is insufficient to explain the under representation of women and minorities in IT careers. Rather, we believe that stratifying the population in a more nuanced manner, such as by gender within ethnic group, provides deeper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 80 publications
1
23
0
Order By: Relevance
“…Since 2000, 50 papers on the topic of under represented groups have appeared in the conference proceedings. But only ten of these papers have considered the topic of race or ethnicity [2,3,4,5,6,7,8,9,10,11]. Trauth's [12] review of papers on the topic gender and IS that were published in IS journals between 1992 and 2012 shows a similar pattern: only two out of 132 journal articles addressed the topic of race or ethnicity [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2000, 50 papers on the topic of under represented groups have appeared in the conference proceedings. But only ten of these papers have considered the topic of race or ethnicity [2,3,4,5,6,7,8,9,10,11]. Trauth's [12] review of papers on the topic gender and IS that were published in IS journals between 1992 and 2012 shows a similar pattern: only two out of 132 journal articles addressed the topic of race or ethnicity [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…We conducted interviews with 20 IT majors at two HBCUs to uncover how their perspectives about and interest in IT careers are constructed within their cultural realities and experiences. Prior research has found that African American males' career development and choices unfold differently than for African American women and other ethnic male cohorts [6,17,18,19]. Our analysis is guided by a digital inequality framework, which posits that an individual's access to equipment, skills, social support, purpose of use, and autonomy of use will shape their relationship with technology.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, females are often discouraged from taking up technology-related subjects and interests and their expertise in these areas may be under-valued [12]. These gender-based norms put pressure on men and women to conform to prescribed normative roles [8]. With the technology emphasis in IT subjects, as girls grow up, they may be less likely to choose an IT major to study [13].…”
Section: Gender and It Careermentioning
confidence: 99%
“…According to the social constructionist perspective, individuals' perceptions are socially constructed, accepted, and internalized. Thus, men are socially perceived to be well-suited to perform stereotypically masculine roles whereas women are viewed to fit well in stereotypically feminine roles [8].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation